Essential oils in the treatment of anxiety: indications and methods of use - Carnavali, Larissa Marcelino; Silva, Talita Oliveira da; Arakawa, Janice Aparecida Rafael (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 40 No especial (2024): Estética e Cosmética, 2024)
This articlehas as main goal to observe the factors of recovery, treatment and improvement of Anxiety symptoms through the application of Aromatherapy, being a work of literature review and bibliographic research. The proposal consists of observing the definition of anxiety, as well as the effects of anxiety on the body, seeing how aromatherapy can help in the treatment of these patients, observing what essential oils are, their means of production and their main benefits and characteristics, in addition to to explore how they are applied, finally, it seeks to understand through the analysis of other texts with physical tests on patients, how essential oils have helped in the treatment and recovery of people with anxiety, observing the results obtained in these researches and updating the scenario on the application and indication of essential oils in the treatment of people with anxiety.